Aktivitas antibakteri mucus siput darat (terestrial snails): review - I Gusti Ayu Agung Septiari; Ni Putu Aryati Suryaningsih (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
Antibiotic resistance is one of the major health problems faced by many countries around the world. Due to the urgency of antibiotic resistance, efforts to identify new lead compounds from novel sources and analyses to determine their bioactivity are highly needed for antibiotic development. One of the invertebrate organisms studied for its potential to produce secondary metabolites with antibacterial properties is the class Gastropoda within the phylum Mollusca. Gastropods consist of more than 80 thousand species and differ from other classes in the phylum Mollusca due to their torsioned body. Gastropods have three subclasses, namely Prosobranchia, Opisthobranchia, and Pulmonata. One of the terrestrial gastropod species is snails, which include those with shells (snails) and shell-less snails (slugs), belonging to the subclass Pulmonata. Mucus from snails is utilized as traditional medicine and as an innovative natural product to treat various health problems. Since Gastropoda includes a large number of species distributed across various ecosystems, but research on the antibacterial potential of their secondary metabolites is still limited, this review aims to summarize studies exploring the antibacterial effects of secondary metabolites in the mucus produced by terrestrial gastropod species, particularly various species of terrestrial shelled snails (terrestrial snails). The preparation of this review article uses a literature study method with a systematic approach. The articles used are international articles discussing the antibacterial activity of secondary metabolites in the mucus produced by terrestrial shelled snails (snails). Articles were obtained from the PubMed database using the keywords snails AND antibacterial from the period 2000 to 2023; the period before 2000 was excluded due to the very limited number of articles. The results obtained from the journal review indicate the presence of bioactive components such as peptides, glycopeptides, and other secondary metabolites found in the mucus of several terrestrial snail species. These bioactive components exhibit antibacterial activity against both gram-positive and gram-negative bacteria.